Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a) -6x + 3(7 + 2x)
= -6x + 21 + 6x
= (-6x + 6x) + 21
= 21
b) 15y - 5(6x + 3y)
= 15y - 30 - 15y
= (15y - 15y) - 30
= -30
c) x(2x + 1) - x2(x + 2) + (x3 - x + 3)
= 2x2 + x - x3 - 2x2 + x3 - x + 3
= (2x2 - 2x2) + (x - x) + (-x3 + x3) + 3
= 3
d) x(5x - 4)3x2(x - 1) ??? :V
Bài 2:
a) 3x + 2(5 - x) = 0
<=> 3x + 10 - 2x = 0
<=> x + 10 = 0
<=> x = -10
=> x = -10
b) 3x2 - 3x(-2 + x) = 36
<=> 3x2 + 2x - 3x2 = 36
<=> 6x = 36
<=> x = 6
=> x = 5
c) 5x(12x + 7) - 3x(20x - 5) = -100
<=> 60x2 + 35x - 60x2 + 15x = -100
<=> 50x = -100
<=> x = -2
=> x = -2
\(x^2-4xy-y^2=\left(x^2-4xy+y^2\right)-2y^2\)
\(=\left(x-y\right)^2-\left(\sqrt{2}.y\right)^2\)
\(=\left(x-y-\sqrt{2}.y\right)\left(x-y+\sqrt{2}y\right)\)
\(x^4-\frac{1}{2}=\left(x^2\right)^2-\left(\sqrt{\frac{1}{2}}\right)^2=\left(x^2-\sqrt{\frac{1}{2}}\right)\left(x^2+\sqrt{\frac{1}{2}}\right)\)
1) ADTCDTSBN, ta có:
\(\frac{x}{3}=\frac{y}{4}=\frac{z}{5}\)= \(\frac{2x^2+2y^2-3z^2}{18+32-75}=\frac{-100}{-25}\)= 4
* \(\frac{x}{3}=4\)=> x = 3 . 4 = 12
- \(\frac{y}{4}=4\)=> y = 4 . 4 = 16
* \(\frac{z}{5}=4\)=> z = 5 . 4 = 20
Vậy x = 12
y = 16
z = 20
Trả lời nhanh giúp mik ạ